2018
DOI: 10.1002/slct.201802251
|View full text |Cite
|
Sign up to set email alerts
|

A Green and Efficient Synthesis of Bioactive 1, 2, 3 ‐ Triazolyl‐Pyridine/Cyanopyridine Hybrids via One‐Pot Multicomponent Grinding Protocol

Abstract: A green and efficient synthesis of bioactive 1,2,3‐triazolyl‐pyridine/cyanopyridine hybrids has been achieved from easily accessible starting materials via one‐pot sequential multicomponent reaction under grinding strategy at room temperature in good to excellent yields. All the synthesized hybrids were evaluated for their antimicrobial activities against three human bacterial pathogens viz. Staphylococcus aureus, Salmonella typhi and Escherichia coli. The 1,2,3‐triazolyl cyanopyridine hybrids with 4‐chlorophe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Jaabil et al [ 17 ] have studied the in vitro antimicrobial activities of some newly hybrid 1,2,3-triazolo-pyridine derivatives. The synthesis was green and efficient, under grinding strategy at room temperature, involving one-pot sequential multicomponent reactions of aryl aldehydes 32a – r , malonitrile 33 , methanol and 1,2,3-triazolyl ketone 34 , when the corresponding 1,2,3-triazolyl-pyridine/cyanopyridine hybrids 35a – r were obtained, Scheme 9 .…”
Section: Resultsmentioning
confidence: 99%
“…Jaabil et al [ 17 ] have studied the in vitro antimicrobial activities of some newly hybrid 1,2,3-triazolo-pyridine derivatives. The synthesis was green and efficient, under grinding strategy at room temperature, involving one-pot sequential multicomponent reactions of aryl aldehydes 32a – r , malonitrile 33 , methanol and 1,2,3-triazolyl ketone 34 , when the corresponding 1,2,3-triazolyl-pyridine/cyanopyridine hybrids 35a – r were obtained, Scheme 9 .…”
Section: Resultsmentioning
confidence: 99%
“…[79] Jabil et al reported 1,2,3-triazolyl cyanopyridine hybrids 29 a-m (Figure 8) by simple grinding techniques. [80] Compounds 29 c and 29 e demonstrated significant antibacterial activity against S. aureus and E. coli, outperforming commercial control tetracycline. They also outperformed tetracycline against S. Typhi and E. coli, demonstrating substantial antibacterial activity against all three human pathogenic microorganisms.…”
Section: Antimicrobialmentioning
confidence: 98%
“…[4] Hereafter, we adopted the mortarpestle grinding mechanochemistry method, one of the most efficient, economical, rapid, handy, sustainable, convenient, and effective synthetic strategies. [5] The literature survey, multicomponent mechanochemical preparation, [6] catalyst-free synthesis of pyridines via a multicomponent grinding tool, [7] small organic molecules designed by solid-phase synthesis, [8] multicomponent mechanochemical synthesis of titanium tertiary butyl halides, [9] and assembly of triazolochromenes through multicomponent reactions by mechanochemical process [10] have revealed the importance of the mortar and pestle mechanochemical grinding process. Also, a few other research articles, i. e., solvent and catalyst-free multicomponent synthesis of dihydropyridines, [11] the Biginelli reaction under solvent-free grinding processes, [12] catalyst and solventfree multicomponent synthesis of indoloindole pyrimidine, [13] and physicochemical characterised inorganic catalyst usage in multicomponent synthesis, [14] uncover the usage of green solvents for multicomponent synthesis through mortar-pestle grinding mechanochemical methods emphasizing the green solvent significance.…”
Section: Introductionmentioning
confidence: 99%
“…[32] The earlier research on this type of core structure construction involved the usage of organic solvents, catalysts, traditional methodologies, tedious and expensive. L. Rong et al, have synthesized 2-amino-4aryl-6,7,8,9-tetrahydro-5H-benzo [7] annulene-1,3-dicarbonitriles using THF as a solvent and DBU as a catalyst, which consumed 2 h of time in reflux conditions. [33] Pagadala et al, utilized water as a solvent with a Zn-VCO 3 catalyst for multifunctionalized benzene derivative preparation and obtained the products in 2 h in a reflux setup at 80 °C.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation